Innovative Ways of Dealing With Menstrual Health Among the Marginalized Communities in Kenya. - Birech, Jeniffer Kosgey (Advances in Social Sciences Research Journal, 2019)
Globally, there are 1.8 billion young people and the majority live in developing countries. Approximately half of them about 900 million are adolescent girls and young women. Notably, the adolescent girls have huge untapped potential, unfortunately most of them are marginalized and vulnerable. This paper discusses menstrual health challenges facing the adolescent girls and innovative ways of dealing with it. Menstruation is a natural process that every woman experience in her life time. More particularly, it is one of the physical changes that occur in girls at the start of puberty. However, in the developing countries menstruation is associated with myths and beliefs which lead to feelings of shame, stigma and anxiety. Besides, the girls lack adequate knowledge on how to handle menarche and the prohibitive costs of sanitary pads. Worldwide, studies have reported that more than 50% of girls have inadequate menstrual health facilities with high proportions reported in the rural areas. In Sub Saharan Africa, it is estimated that one in ten girls misses school during menstruation. In Ghana, it is estimated that 11.5 million women experience poor sanitation. In Kenya, 1 million girls miss over six weeks of school in a year due to lack of access to affordable sanitary pads. The marginalized communities are adversely affected. Innovative ways of dealing with menstrual health have come up though it experiences inadequate coordination, funding and awareness. In Rwanda, Sustainable Enterprises is working with communities to turn discarded banana fibers into affordable biodegradable sanitary pads and provides menstrual education. In Kenya, Zana Africa uses local agricultural products to produce affordable sanitary products. The use of menstrual cup has been associated with fears such as loss of virginity, cultural beliefs that forbid girls from touching their reproductive organs, limited resources such as soap and water. The paper recommends that awareness need to be created on the existence of innovative products, linkages and partnerships to be enhanced to ensure that the girl has access to the facilities. Beyond that, there is need for investment in research to unearth more sustainable products. Finally, a multipronged approach that encompasses government institutions, community, parents and development partners should be adopted. This enhances effective sustainable solutions.